Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve for the composite function [tex]\((g \circ f)(x)\)[/tex], we need to apply the function [tex]\(f(x)\)[/tex] first and then apply the function [tex]\(g(x)\)[/tex] to the result of [tex]\(f(x)\)[/tex].
1. Define [tex]\( f(x) \)[/tex]:
[tex]\( f(x) = 6x - 4 \)[/tex]
2. Define [tex]\( g(x) \)[/tex]:
[tex]\( g(x) = 2x^2 + 5 \)[/tex]
3. Find [tex]\( f(x) \)[/tex]:
[tex]\( f(x) = 6x - 4 \)[/tex]
4. Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\( g(f(x)) = g(6x - 4) \)[/tex]
5. Evaluate [tex]\( g(6x - 4) \)[/tex]:
Substitute [tex]\( 6x - 4 \)[/tex] into [tex]\( g \)[/tex]:
[tex]\( g(6x - 4) = 2(6x - 4)^2 + 5 \)[/tex]
6. Expand [tex]\( (6x - 4)^2 \)[/tex]:
[tex]\((6x - 4)^2 = 36x^2 - 48x + 16\)[/tex]
7. Multiply the result by 2:
[tex]\( 2 \cdot (36x^2 - 48x + 16) = 72x^2 - 96x + 32 \)[/tex]
8. Add 5 to the result:
[tex]\( 72x^2 - 96x + 32 + 5 = 72x^2 - 96x + 37 \)[/tex]
Therefore, the composite function is:
[tex]\[ (g \circ f)(x) = 72x^2 - 96x + 37 \][/tex]
1. Define [tex]\( f(x) \)[/tex]:
[tex]\( f(x) = 6x - 4 \)[/tex]
2. Define [tex]\( g(x) \)[/tex]:
[tex]\( g(x) = 2x^2 + 5 \)[/tex]
3. Find [tex]\( f(x) \)[/tex]:
[tex]\( f(x) = 6x - 4 \)[/tex]
4. Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\( g(f(x)) = g(6x - 4) \)[/tex]
5. Evaluate [tex]\( g(6x - 4) \)[/tex]:
Substitute [tex]\( 6x - 4 \)[/tex] into [tex]\( g \)[/tex]:
[tex]\( g(6x - 4) = 2(6x - 4)^2 + 5 \)[/tex]
6. Expand [tex]\( (6x - 4)^2 \)[/tex]:
[tex]\((6x - 4)^2 = 36x^2 - 48x + 16\)[/tex]
7. Multiply the result by 2:
[tex]\( 2 \cdot (36x^2 - 48x + 16) = 72x^2 - 96x + 32 \)[/tex]
8. Add 5 to the result:
[tex]\( 72x^2 - 96x + 32 + 5 = 72x^2 - 96x + 37 \)[/tex]
Therefore, the composite function is:
[tex]\[ (g \circ f)(x) = 72x^2 - 96x + 37 \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.